Long‐term outcomes and quality of life following ligation of the intersphincteric fistula tract for high transsphincteric fistulas. (21st November 2018) - Sun, X.‐L.; Wen, K.; Chen, Y.‐H.; Xu, Z.‐Z.; Wang, X.‐P.
Abstract: Aim: Published outcomes following ligation of the intersphincteric fistula tract (LIFT) for high transsphincteric fistulas (HTFs) are equivocal probably because most trials are small and comprise mixed patient populations. The aim of this study was to highlight the long‐term efficacy of LIFT for HTFs in a large homogeneous sample and to determine the risk factors that contribute to non‐healing resulting in failure and recurrence. Method: A retrospective study was performed which assessed patients with HTFs treated by LIFT without prior loose setons from September 2012 to December 2017. Continence function was evaluated by the Wexner incontinence scale and anal manometry. Quality of life was assessed by using the faecal incontinence quality of life (FIQL) scale with four domains: lifestyle, coping, depression and embarrassment. Results: Seventy patients with HTFs underwent 71 LIFT procedures. The primary healing rate was 81.7% with a median follow‐up duration of 16.5 (range 4.5–68) months. The healing rates of mature and immature fistulas were 83.7% and 77.3%, respectively. Two patients suffered failure with an unhealed intersphincteric wound. Recurrence occurred in 11 patients. Incontinence of flatus, present in four patients before surgery, improved postoperatively. Two patients undergoing LIFT combined with fistulotomy complained of flatus incontinence after surgery. No significant differences between preoperative and postoperative Wexner score, maximum resting pressure and maximum squeeze pressure were detected. The FIQL was improved in lifestyle, coping and depression. No risk factor for non‐healing was found. Conclusion: LIFT has a promising long‐term outcome for HTFs, with negligible impairment on continence and improved quality of life.